An Efficient, "Burn in" Free Organic Solar Cell Employing a Nonfullerene Electron Acceptor. Issue 33 (28th June 2017) - Cha, Hyojung; Wu, Jiaying; Wadsworth, Andrew; Nagitta, Jade; Limbu, Saurav; Pont, Sebastian; Li, Zhe; Searle, Justin; Wyatt, Mark F.; Baran, Derya; Kim, Ji‐Seon; McCulloch, Iain; et al.
Abstract : A comparison of the efficiency, stability, and photophysics of organic solar cells employing poly[(5, 6‐difluoro‐2, 1, 3‐benzothiadiazol‐4, 7‐diyl)‐alt‐(3, 3′″‐di(2‐octyldodecyl)‐2, 2′;5′, 2″;5″, 2′″‐quaterthiophen‐5, 5′″‐diyl)] (PffBT4T‐2OD) as a donor polymer blended with either the nonfullerene acceptor EH‐IDTBR or the fullerene derivative, [6, 6]‐phenyl C71 butyric acid methyl ester (PC71 BM) as electron acceptors is reported. Inverted PffBT4T‐2OD:EH‐IDTBR blend solar cell fabricated without any processing additive achieves power conversion efficiencies (PCEs) of 9.5 ± 0.2%. The devices exhibit a high open circuit voltage of 1.08 ± 0.01 V, attributed to the high lowest unoccupied molecular orbital (LUMO) level of EH‐IDTBR. Photoluminescence quenching and transient absorption data are employed to elucidate the ultrafast kinetics and efficiencies of charge separation in both blends, with PffBT4T‐2OD exciton diffusion kinetics within polymer domains, and geminate recombination losses following exciton separation being identified as key factors determining the efficiency of photocurrent generation. Remarkably, while encapsulated PffBT4T‐2OD:PC71 BM solar cells show significant efficiency loss under simulated solar irradiation ("burn in" degradation) due to the trap‐assisted recombination through increased photoinduced trap states, PffBT4T‐2OD:EH‐IDTBR solar cell shows negligible burn in efficiency loss. Furthermore, PffBT4T‐2OD:EH‐IDTBR solar cells are found to be substantially more stable under 85 °C thermal stress than PffBT4T‐2OD:PC71 BM devices. Abstract : A high efficiency, burn‐in‐free nonfullerene‐based PffBT4T‐2OD:EH‐IDTBR solar cell is reported, fabricated without processing additives. Transient absorption and optoelectronic analyses elucidate the causes of this high efficiency and stability, with the superior stability compared to PC71 BM devices being correlated with increased crystallinity and reduced photogeneration of trap states.